Research progress of oral cold therapy combined with Kangfuxin liquid in prevention and treatment of oral mucositis caused by radiotherapy and chemotherapy (口腔冷疗联合康复新液防治放化疗所致口腔黏膜炎的研究进展) - TAN Xiaoqi (谭小琪); LI Qin (李勤); ZHANG Guilan (张桂兰) (Association of Integrative Nursing, 2021)
Cancer patients are prone to deterioration of oral health during the treatment. Oral mucosal damage after radiotherapy and chemotherapy is a difficult challenge for medical workers, patients and their caregivers. This article reviewed the research progress of oral cold therapy and Kangfuxin liquid in prevention and treatment of oral mucositis caused by radiotherapy and chemotherapy, and provided better prevention and treatment methods for guiding oral mucositis caused by radiotherapy and chemotherapy. (癌症患者在治疗过程中易呈现出口腔健康状况恶化的情况。放化疗所致口腔黏膜损伤的防治对医护人员、患者及其照护者是一项艰难的挑战。本文综述口腔冷疗和康复新液防治放化疗所致口腔黏膜炎的研究进展, 为指导放化疗所致口腔黏膜炎提供更好的预防和治疗方法。)